ISSUES OF APPLICATION OF INTERNATIONAL AUDITING AND ASSURANCE STANDARDS BOARD (IAASB) IN UZBEKISTAN (Journal of Science-Innovative Research in Uzbekistan, 2024)
The International Auditing and Assurance Standards Board (IAASB) sets global standards for auditing and assurance to enhance the quality and consistency of audit practices worldwide. This article examines the issues and challenges in applying IAASB standards in the context of Uzbekistan. Through a review of relevant literature and analysis of the current audit environment in Uzbekistan, we identify several key factors impacting IAASB implementation, including the existing legal and regulatory framework, translation and interpretation of the standards, auditor training and capacity, and enforcement mechanisms.